2004
DOI: 10.1139/t03-098
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reaction piles on the behaviour of a test pile in static load testing

Abstract: This paper employs a simplified analytical method to investigate the influence of reaction piles on the load-displacement behaviour of the test pile in static load testing. A parametric study is conducted to examine the effects of factors such as pile spacing ratio, pile slenderness ratio and pile soil stiffness ratio. Several soil profiles are considered in this study.The parametric study also includes the cases of static load testing in lateral direction. The correction factors for the initial pile head stif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
(4 reference statements)
0
11
0
4
Order By: Relevance
“…To verify the reliability of the present approach, the above-mentioned approach is used to analyze the test pile embedded in two soil profiles reported by Kitiyodom et al (2004), as shown in Fig. 3.…”
Section: Comparison Of Computed Results Derived From the Present Apprmentioning
confidence: 99%
See 4 more Smart Citations
“…To verify the reliability of the present approach, the above-mentioned approach is used to analyze the test pile embedded in two soil profiles reported by Kitiyodom et al (2004), as shown in Fig. 3.…”
Section: Comparison Of Computed Results Derived From the Present Apprmentioning
confidence: 99%
“…3. Comparisons of results are made between the proposed approach and the program PRAB (Kitiyodom et al, 2004) for both cases. Note that the emphases of both cases are focused on the relationship between load and displacement (initial pile head stiffness) where the subsoil behaves linear elastically.…”
Section: Comparison Of Computed Results Derived From the Present Apprmentioning
confidence: 99%
See 3 more Smart Citations